Collaborative energy districts – Urban workshops for proximity energy - Davide Crippa; Barbara Di Prete; Raffaella Fagnoni; Carmelo Leonardi (Agathón)
Demands for energy sustainability have become a priority, and institutional policies are incentivising alternative energy production models over established ones. Cities consume over 65% of the world’s resources and are strategic. Within this framework, the essay analyses some experimental urban laboratories and potential incubators of innovative policies for energy transition; these are climate-neutral pioneer districts investing in inclusive processes, local energy markets, and active citizenship, promoting conscious and virtuous energy behaviour. These projects pursue a greater empowerment of individuals and take the concepts of ‘community’ and ‘proximity’ as a strategic perspective.